Advanced Compatibility Testing Strategies for Patients with Multiple Alloantibodies: Clinical Challenges and Management Solutions - Ranjan, Shweta; Das, Bankim; Nayan, Nishith; Kumar, Rakesh (Achievements and Challenges of Medicine and Medical Science Vol. 7, 2024)
Providing safe blood to the recipients is the most important responsibility of blood transfusion services. Pre-transfusion testing which includes compatibility testing between donor red cells and recipient’s serum is a crucial step in this provision of safe blood. Multiple transfusions can potentially lead to alloimmunization resulting in delayed hemolysis in recipients. This makes it difficult for blood transfusion services to find cross-match compatible red cell units especially when antibodies against “Kidd” antigens are present in recipients which are clinically significant and known to cause evanescence. Rates of red cell alloimmunisation throughout the world has been found to be between 2.6 to 9%. The study aimed to optimize the management of anaemic patients who present with multiple alloantibodies. We present a case of a 43-year-old female who presented with anaemia and required two units of packed red cells for transfusion. As per our departmental policy, an antihuman globulin (AHG) cross-match was performed with random red cell units of the same blood group. Since no compatible units could be found, the patient’s antibody screening and identification were carried out and the presence of anti-Fya and anti-Jkb alloantibodies was confirmed at the AHG phase. Donor red cell units were phenotyped and Fya and Jkb antigens negative units were issued to the patient. Her haemoglobin levels improved, and she did not require additional PRBC transfusions during her hospital stay. Patients with multiple alloantibodies can be managed by applying advanced immunohematological techniques for identifying those alloantibodies and providing the corresponding antigen-negative PRBCs thus ensuring safe transfusion.